The Effect of Customer Engagement, Content Personalization, and Trust on Purchasing Decisions in Indonesian E-commerce: A Case Study on the Fashion Industry - Suryati, Suryati; Sari, Efti Novita; Utami, Eva Yuniarti (West Science Journal Economic and Entrepreneurship, 2023)
An in-depth understanding of the elements influencing consumer behavior is necessary given the constantly changing environment of e-commerce in the Indonesian fashion industry. This study looks into how trust, content personalization, and customer engagement affect consumers' decisions to buy. Using Structural Equation Modeling, a quantitative analysis examines a sample that reflects the heterogeneous consumer base of Indonesian e-commerce. The measuring model demonstrates strong psychometric qualities, and analyses of discriminant validity attest to the latent constructs' uniqueness. Fit indices support the structural equation model's suitability, while regression analysis demonstrates the importance of trust, content personalization, and customer engagement in influencing purchase decisions. Future research directions and their practical implications for enterprises are highlighted.